Association between potential parental and peers' correlates and physical activity recommendations compliance among 13-16 years old adolescents - Peter Bakalár; Jaroslava Kopčáková; Andrea Madarasová Gecková (Palacký University Olomouc, 2019)
Background: Regular physical activity (PA) is one of the most cited health protective factors for the prevention of the leading noncommunicable diseases. Four-fifths of adolescents are not reaching public health guidelines for recommended levels of PA globally. Understanding factors that influence PA can aid the design of more effective interventions. Objective: The aim of the study was to assess the association between potential parental and peer correlates and PA recommendations compliance among 13-16 years old adolescents. Methods: We used nationally representative data originated from the Health Behaviour in School-aged Children survey realized in 2014 in Slovakia. Data were obtained by questionnaires measuring potential parental and peers' correlates. Gender differences were assessed using chi square test. The associations between potential parental or peers' correlates and moderate-to-vigorous PA (MVPA) of adolescents were explored using logistic regression models adjusted for gender, age, and family affluence. Interaction of the effect of each parental and peer correlate with gender on MVPA was tested. Results: Prevalence of sufficient MVPA was higher among boys than among girls (p < .001). Boys reported more frequently than girls that their best friend does sport every week or that they used to play sport with parents at least once a week (p < .001). All explored variables representing potential parental and peers' correlates were significantly associated with sufficient MVPA of adolescents. However, only the association of a best friend and father doing sport every week and playing sport with parents remained significantly associated with sufficient MVPA of adolescents in mutually adjusted model. Conclusion: Our findings indicate that best friends and fathers may play role in PA behaviour of adolescents through behaviour modelling, and parents in general through tangible parental support (playing sport with children).